Islamic Art Innovation in Jelekong Paintings for Strengthening the Creative Economy - Agus Cahyana; Asep Miftahul Falah; Martien Roos Nagara (PANTUN: Jurnal Ilmiah Seni Budaya, 2026)
This community service project aimed to enhance the competitiveness of Jelekong Village painters through the application of Islamic decorative motifs in painting production. The program was based on the concept of Islamic decorative art, which emphasizes calligraphy, geometric patterns, and floral ornamentation as visual expressions of Islamic values. The study employed a Participatory Action Research (PAR) approach involving local painters in Jelekong Village, Bandung Regency. Data were collected through observation, interviews, training activities, and participant evaluation. The implementation consisted of five stages: knowing, understanding, planning, action, and reflection (KUPAR). The results indicated that participants improved their understanding of Islamic decorative motifs, acquired new skills in producing Islamic-themed paintings, and increased their ability to utilize digital marketing platforms. The introduction of graphic reproduction techniques and digital promotion strategies also improved production efficiency and expanded market opportunities among Muslim consumers. The program contributed to product diversification and strengthened the creative economy of the Jelekong painting community.